LncRNA CASC11 Promotes Hepatocellular Carcinoma Progression via Upregulation of UBE2T in a m6A-Dependent Manner - Chen, Fei; Li, Meijun; Wang, Liang (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of the most frequent malignancies and the third leading cause of cancer-related deaths worldwide. Besides, it has been revealed that long non-coding RNA (LncRNA) cancer susceptibility candidate 11 (CASC11) is involved in cancer progression. However, the functional role and underlying mechanism of CASC11 in HCC remains largely unknown. In this context, here, it was found that CASC11 was upregulated in HCC tissues and associated with tumor grades, metastasis, and prognosis of HCC patients. Functionally, CASC11 facilitated HCC cell proliferation, migration, and invasion in vitro, and enhanced tumor growth and metastasis in vivo. Mechanistically, CASC11 associated with and stabilized Ubiquitin-conjugating enzyme E2T (UBE2T) mRNA. To be specific, it decreased UBE2T N6-methyladenosine (m6A) level via recruiting ALKBH5. Moreover, CASC11 inhibited the association between UBE2T mRNA and m6A reader protein YTHDF2. Taken together, our findings demonstrate the epigenetic mechanism of CASC11 in the regulation of UBE2T expression and possibly provide a novel therapeutic target for HCC treatment.